Effect of the topical administration of N-(2-(4-bromophenylamino)-5-(trifluoromethyl)phenyl)nicotinamide compound in a murine subcutaneous melanoma model. Issue 7 (August 2020) - Vale, Juliana Alves do; de Souza, Ana Paula Martins; Lima, Graziela Domingues Almeida; Gonçalves, Victor Hugo Sousa; Moreira, Gabriela Alves; Barros, Marcus Vinícius de Andrade; Pereira, Wagner Luiz; Merchid, Nara Clara Lazaroni e; Fietto, Juliana Lopes Rangel; Bressan, Gustavo Costa; Teixeira, Róbson Ricardo; Machado-Neves, Mariana
Abstract : Conventional treatments for metastatic melanomas are still ineffective and generate numerous side effects, justifying the search for new therapies. The antimetastatic effect of the named N-(2-(4-bromophenylamino)-5-(trifluoromethyl)phenyl)nicotinamide (SRVIC30) compound has been previously demonstrated in murine melanoma. Herein, we aimed to evaluate its effect when topically administrated in a murine subcutaneous melanoma model. For that, mice C57BL/6 were injected subcutaneously with 2 × 10 5 B16-F10 cells. Topical treatment began when tumors became visible on animal's back. Therefore, tumor volume was measured three times a week until it reaches 12 mm 3 approximately. At this point, 40 mg oil-in-water cream (Lanette) without (control mice; n  = 10) or with SRVIC30 compound (SRVIC30 group; n  = 10 animals) were spread daily over the tumor external surface using a small brush for 14 days. The treatments increased the percentage of peroxidase antioxidant enzyme and dead cells via caspase-3 activation, with a consequent deposit of collagen fibers in the tumors. In addition, the skin of treated animals showed the presence of inflammatory infiltrate. Finally, SRVIC30 did not show signs of toxicity. Thus, we concluded that the topic administration of SRVIC30 was able to influence crucial anticancer processes such as tumor cells apoptosis and surrounding microenvironment.